Pathophysiological Mechanisms of Gastro-esophageal Reflux After Sleeve Gastrectomy. Issue 5 (18th November 2022) - Johari, Yazmin; Lim, Gillian; Wickremasinghe, Anagi; Yue, Helen; Seah, Jarrel; Ooi, Geraldine; Playfair, Julie; Laurie, Cheryl; Beech, Paul; Yap, Kenneth; Hebbard, Geoff; Brown, Wendy; et al.
Abstract : Objective: To evaluate the mechanisms associated with reflux events after sleeve gastrectomy (SG). Summary Background Data: Gastro-esophageal reflux (GERD) post-SG is a critical issue due to symptom severity, impact on quality of life, requirement for reoperation, and potential for Barrett esophagus. The pathophysiology is incompletely delineated. Methods: Post-SG patients, stratified into asymptomatic and symptomatic, underwent protocolized nuclear scintigraphy (n = 83), 24-hour esophageal pH monitoring, and stationary manometry (n = 143) to characterize reflux patterns. Ten patients underwent fasting and postprandial concurrent manometry and pH for detailed analysis of reflux events. Results: Baseline demographics between cohorts were similar: Age 47.2 ± 11.6 versus 44.1 ± 11.3 years ( P = 0.121); females 73.2% versus 90.8% ( P = 0.005); excess weight loss 53.8 ± 28.1% versus 57.4 ± 25.5% ( P = 0.422), follow-up duration 12.3 versus 7.4 months ( P = 0.503). Nuclear scintigraphy delineated bolus-induced deglutitive reflux events (29.6% vs 62.5%, P = 0.005) and postprandial reflux events [4 (IQR2) versus 4 (IQR 3) events, P = 0.356]. Total acid exposure was significantly elevated in the symptomatic population (7.7% vs 3.6%, P < 0.001), especially fasting acid exposure (6.0% vs 1.3%, P < 0.001). pH/manometry analysis demonstrated acute elevations of the gastro-esophageal pressure gradient (>10 mm Hg) underpinned most reflux events. Swallow-induced intragastric hyper-pressur-ization was associated with individual reflux events in most patients (90% in fasting state and 40% postprandial). Conclusions: We found reflux to be strongly associated with SG and identified 3 unique categories. Bolus-induced deglutitive and postprandial reflux occurred in most patients. Elevated fasting esophageal acid exposure mediated symptoms. Frequent, significant elevation in the gastro-esophageal pressure gradient was the mechanism of reflux and seemed to relate to the noncompliant proximal stomach.